2019
DOI: 10.1007/s12094-018-02023-5
|View full text |Cite
|
Sign up to set email alerts
|

The RANK–RANKL axis: an opportunity for drug repurposing in cancer?

Abstract: Drug repurposing offers advantages over traditional drug development in terms of cost, speed and improved patient outcomes. The receptor activator of nuclear factor kappa B (RANK) ligand (RANKL) inhibitor denosumab is approved for the prevention of skeletal-related events in patients with advanced malignancies involving bone, including solid tumours and multiple myeloma. Following improved understanding of the role of RANK/RANKL in cancer biology, denosumab has already been repurposed as a treatment for giant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 96 publications
1
33
0
Order By: Relevance
“…Furthermore, numerous studies have demonstrated RANKL and RANK expression in neoplastic tissues. Interestingly, the expression level of RANKL/RANK in cancer tissues is related to the prognosis of numerous cancer types, including breast, lung, endometrial, renal cell, and gastric cancer [99]. Therefore, the RANKL/RANK axis may influence the development and progression of cancer, while the specific effects of RANKL/RANK may differ between cancer types.…”
Section: Rankl In Tumorigenesis and Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, numerous studies have demonstrated RANKL and RANK expression in neoplastic tissues. Interestingly, the expression level of RANKL/RANK in cancer tissues is related to the prognosis of numerous cancer types, including breast, lung, endometrial, renal cell, and gastric cancer [99]. Therefore, the RANKL/RANK axis may influence the development and progression of cancer, while the specific effects of RANKL/RANK may differ between cancer types.…”
Section: Rankl In Tumorigenesis and Metastasismentioning
confidence: 99%
“…4d) [107,108]. The RANKL/RANK/OPG system is known to be involved in the development and metastasis of breast cancer, lung cancer, prostate cancer, melanoma, and renal cell carcinoma [99,107]. In addition, the relative expression levels of (See figure on previous page.)…”
Section: Bone Metastasismentioning
confidence: 99%
“…12,13 RANK and RANKL are increased in tumors and expressed by various immune cell types in the TME, including RANK by tumor-infiltrating myeloid cells (TAMCs) and RANKL expression variously by CD8 + and CD4 + T cells, tumor cells and other stromal components. 12,13 RANK and RANKL are increased in tumors and expressed by various immune cell types in the TME, including RANK by tumor-infiltrating myeloid cells (TAMCs) and RANKL expression variously by CD8 + and CD4 + T cells, tumor cells and other stromal components.…”
Section: Introductionmentioning
confidence: 99%
“…Recent preclinical and clinical evidence supports a potential for RANKL/RANK antagonism to enhance anti-tumor immunity, particularly in combination with ICI. 12,13 RANK and RANKL are increased in tumors and expressed by various immune cell types in the TME, including RANK by tumor-infiltrating myeloid cells (TAMCs) and RANKL expression variously by CD8 + and CD4 + T cells, tumor cells and other stromal components. 7,12 The combination treatment of anti-RANKL mAb with immune checkpoint blockade (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of new compounds into clinical practice is both, time constraining and a financial endeavour, which more often than not is subject to failure. Drug repurposing brings a selective advantage to the field of drug discovery as it is easier and more costeffective to authorize the approved drug for a new indication 9 .…”
Section: Introductionmentioning
confidence: 99%